Enhancing nursing competency through virtual reality simulation among nursing students: a systematic review and meta-analysis - Cho, Mi-Kyoung; Kim, Mi Young (Frontiers in Medicine, 2024)
Aim Studies on the effectiveness of virtual reality (VR) in nursing education have explored its impact on learning outcomes, emotional immersion and engagement, learner self-confidence, and satisfaction, generally showing positive aspects. However, there is a need for a systematic review to examine the specific influence of VR-based education on nursing students’ practical competency. Method According to the PRISMA 2020 guidelines, 22 studies were selected based on inclusion criteria from 579 articles, published from January 1, 2018, to March 31, 2024, across nine major databases including PubMed and EMbase. The target population comprised nursing students, and the intervention focused on VR-based simulations aimed at enhancing competency, compared to control groups receiving either no intervention or conventional non-virtual simulation. The primary outcome, nursing competency, was analyzed using MIX 2.0 Pro (Ver. 2.0.1.6, BiostatXL, 2017) to calculate pooled effect sizes. Result The pooled effect size for nursing competency was determined to be large, with Hedge’s g = 0.88 (95% CI, 0.47 to 1.29). Meta-regression analysis identified several factors associated with an increase in nursing competency. These included studies published after 2022, approval of an IRB, absence of funding, randomized controlled trials (RCTs), interventions reported as shorter than 4 weeks or not reported, sessions fewer than 4 or not reported, session duration under 1 h or not reported, and observational measurement methods. Additional factors enhancing nursing competency were the inclusion of a pre-briefing before simulations, the absence of a debriefing afterward, and the exclusion of other activities during the simulation. Conclusion By combining the results of the included studies, the systematic review and meta-analysis accounted for variations in sample size, study methodology, and independent intervention effects, providing an overall evaluation of the effectiveness of simulation-based education in improving nursing students’ competency. Limitation The selection criteria for the studies analyzed, which included only those published in English or Korean and reported precise means, standard deviations, and sample sizes, could lead to selection bias and limit the generalization of our study results. Systematic review registration PROSPERO International Prospective Register of Systematic Reviews: http://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023446348.